Factores de riesgo que afectan la movilidad articular en pacientes del centro de Rehabilitación Física "Dr. Parménides Montece Rojas" Vinces - Los Ríos. Noviembre 2023-abril 2024. - Ochoa Gómez, Nicole Anahy (2024)
Joint mobility is the capacity of movement of a joint, which can be affected by damage to some or all of the structures that compose it, with the consequent decrease in its functioning. There are risk factors that contribute to damage to the structure and with it its normal activity. The objective of this research is to determine the risk factors present in patients with joint mobility impairment who attend the Dr. Parmenides Montece Rojas physical rehabilitation centre in the parish of Vinces during the period from November 2023 to April 2024. The methodology to be used will be a field study, descriptive, quantitative, observational and transversal, the information will be collected through a questionnaire and the patient's clinical history, the sample will be 41 people attending rehabilitation, of both sexes, and the independent variables will be risk factors such as age. The dependent variable was defined as joint mobility. The data will be processed through the Excel programme and the information will be presented in the form of tables and graphs for a better interpretation of the results.